Transcranial focused ultrasound selectively increases perfusion and modulates functional connectivity of deep brain regions in humans - Kuhn, Taylor; Spivak, Norman M.; Dang, Bianca H.; Becerra, Sergio; Halavi, Sabrina E.; Rotstein, Natalie; Rosenberg, Benjamin M.; Hiller, Sonja; Swenson, Andrew; Cvijanovic, Luka; Dang, Nolan; Sun, Michael; et al. (Frontiers in Neural Circuits, 2023)
Background: Low intensity, transcranial focused ultrasound (tFUS) is a re-emerging brain stimulation technique with the unique capability of reaching deep brain structures non-invasively. Objective/Hypothesis: We sought to demonstrate that tFUS can selectively and accurately target and modulate deep brain structures in humans important for emotional functioning as well as learning and memory. We hypothesized that tFUS would result in significant longitudinal changes in perfusion in the targeted brain region as well as selective modulation of BOLD activity and BOLD-based functional connectivity of the target region. Methods: In this study, we collected MRI before, simultaneously during, and after tFUS of two deep brain structures on different days in sixteen healthy adults each serving as their own control. Using longitudinal arterial spin labeling (ASL) MRI and simultaneous blood oxygen level dependent (BOLD) functional MRI, we found changes in cerebral perfusion, regional brain activity and functional connectivity specific to the targeted regions of the amygdala and entorhinal cortex (ErC). Results: tFUS selectively increased perfusion in the targeted brain region and not in the contralateral homologue or either bilateral control region. Additionally, tFUS directly effected BOLD activity in a target specific fashion without engaging auditory cortex in any analysis. Finally, tFUS resulted in selective modulation of the targeted functional network connectivity. Conclusions: We demonstrate that tFUS can selectively modulate perfusion, neural activity and connectivity in deep brain structures and connected networks. Lack of auditory cortex findings suggests that the mechanism of tFUS action is not due to auditory or acoustic startle response but rather a direct neuromodulatory process. Our findings suggest that tFUS has the potential for future application as a novel therapy in a wide range of neurological and psychiatric disorders associated with subcortical pathology.